Predictors of Success in Selective Laser Trabeculoplasty for Normal Tension Glaucoma - Lee, Jacky W.Y. (Medicine (Baltimore), 2014)
To determine the predictors of success for selective laser trabeculoplasty (SLT) in normal tension glaucoma (NTG). This prospective cohort study recruited subjects with unilateral or bilateral NTG on medication. All subjects received a single session of 360° SLT treatment. SLT success was defined as IOP reduction ≥20% at 1-month. The following covariates were analyzed via univariate and multivariate analyses: age; sex; lens status; presenting, pre-SLT, and post-SLT IOP's; number and type of medications; SLT shots and energy; and pre-SLT investigations. In 60 eyes of 32 subjects with NTG, there were 30 right eyes and 28 left eyes. The success rate of SLT was 61.7%. Using 3 types of anti-glaucoma medications (coefficient = −2.2, OR = 0.1, P = 0.02) and a thicker retinal nerve fiber layer thickness (coefficient = −0.04, OR = 0.96, P = 0.04) were associated with failure (univariate analysis). In multivariate analysis, a higher pre-SLT IOP (coefficient = 1.1, OR = 3.1, P = 0.05) and a lower 1-week IOP (coefficient = −0.8, OR = 0.5, P = 0.04) were associated with success. SLT was successful in over 60% of treated NTG patients. A higher pre-SLT IOP and a greater IOP reduction at 1-week post-SLT were predictors of a successful outcome.